Association of thrombocytopenia with specific organism and mortality in neonatal sepsis - Sharma Chalise, Shiva Prasad; Mishra, Santosh Kumar; Kansakar, Prerana; Shah, Dilip Prasad; Singh, Ambika Kumari (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Neonatal sepsis is one of the leading causes of mortality worldwide. Knowing the association of thrombocytopenia to the specific organism can help to choose the correct antibiotic before a culture sensitivity report becomes available. Hence, this study was planned to find out if thrombocytopenia is associated with any specific type of organism in neonatal sepsis and higher mortality. Method: It was a retrospective observational study done at the neonatal intensive care unit at Patan Hospital. The samples were taken over three years, from April 2018 to March 2021. All culture-positive sepsis within the study period were included. The cases whose files were missing were excluded. Neonatal sepsis was defined as cases where a blood culture was positive for the organism. The data was analyzed using SPSS 16. Result: There were 51 cases whose analysis was done. Klebsiella 25(49.02%) and Acinetobacter 11(21.57%) were the most common organisms. Fifty-nine percent of cases had thrombocytopenia among which 5(10%), 6(12%), and 19(37%) had mild, moderate, and severe thrombocytopenia, respectively. Klebsiella sepsis was significantly associated with thrombocytopenia (p-value 0.001). The sensitivity of Klebsiella to Meropenem and Colistin was 70% and 100% respectively. Mortality was not associated with thrombocytopenia. Conclusion: In the study, thrombocytopenia was associated with Klebsiella sepsis in neonates. Hence, in thrombocytopenic patients with clinical suspicion of sepsis, proper antibiotics to cover Klebsiella should be started empirically till a blood culture report becomes available.